Destination Image Effect, The Atmosphere And Marketing Of Consumer Loyalty Experiential - Rizky Noveliyani; Trias Setyowati; A. Fahrur Rozi (Indonesian Journal of Law and Economics Review, 2020)
This study aims to analyze the variables that Determine the opportunities for consumer loyalty Jember Kolong cafe among the variables of the destination image, location and experiential research is explanatory research marketing.This the which aims to determine the causal relationship between the dependent and independent variables. The sampling technique used is the purposive sampling method, the which is sampling with certain considerations. The consideration of sampling in this study is a minimum age of 17 years and a minimum purchase of 2 times. The Data used in this study are the data of primary and secondary data. The primary sources of data were used in this study through questionnaires and interviews while secondary sources of data were used in this study through scientific journals and literature. The Data analysis method used is multiple linear regression analysis. The results Showed that the destination image, location and experiential marketing had a significant effect on the consumer loyalty of Cafe Kolong Jember.